Mapping the Silent Threat: A Comprehensive Analysis of Chagas Disease Occurrence in Riverside Communities in the Western Amazon - Paixão, Daniela da Silva; Portela Madeira, Fernanda; Costa de Jesus, Adila; Paixão, Hêmilly Caroline da Silva; Camargo, Juliana de Souza Almeida Aranha; Ribeiro, Mariane Albuquerque Lima; José Ramos, Leandro; de Oliveira, Jader; Aristeu da Rosa, João [UNESP]; Bernarde, Paulo Sérgio; Pereira Relvas, Antonieta; Basano, Sergio de Almeida; et al. (MDPI, 2024)
Chagas disease (CD) is a typical tropical illness caused by Trypanosoma cruzi. The objective of this study was to assess the prevalence of Chagas disease in communities in two states of the Brazilian Amazon. Data collection occurred in July in the Alto Juruá region of Acre and in December in the communities of Humaitá, Amazonas, in 2019. A total of 477 participants were included in the study. In the communities of Alto Juruá, triatomine collections and analyses of T. cruzi infection were also carried out. All confirmed cases were found in the state of Acre, resulting in a total prevalence of 1.67. Of these eight cases, seven underwent ECG, all of which were concluded as normal by the physician team’s cardiologists. Seventeen triatomine bugs, all belonging to the Rhodnius genus, were captured. The natural infection rate by T. cruzi was 25% in the Nova Cintra community and 66.67% in the Boca do Moa community (Alto Juruá). This research found that more than 1% of the studied population exhibited positive serological results for Chagas disease in the riverine communities during the study period, representing a small portion of cases among those who have not yet been diagnosed.
Keywords: American Trypanosomiasis; Trypanosoma cruzi and Amazônia; vectors